'Where is the ECG machine?': a quality improvement project using WhatsApp to improve the efficiency in locating shared medical devices in an inpatient unit. Issue 1 (7th February 2022) - Ali, Adnan; Khan, Haroon; Tully, Vicki
Abstract : Access to medical devices are vital to deliver safe patient care. In the context of constrained resources, however, clinical areas often have insufficient basic equipment, which tend to be shared among multiple clinical teams. This can result in delayed patient management and reduced institutional productivity. In our experience, in 2019, while working at Carseview Centre, an inpatient mental health unit in Dundee (National Health Service Tayside), there was only one functioning ECG machine shared between the five wards. Using the work WhatsApp chat, we aimed to facilitate better sharing of the one machine. Plan, do, study, act (PDSA) 1 intervention introduced the project protocol, which encouraged doctors to post a photo of the device after use, captioned with its location. PDSA 2 involved printing a physical copy of the memorandum and attaching it to the machine to prompt further compliance. In PDSA 3, concise photo-posting guidelines were established and adherence was encouraged to mitigate concerns for potential confidential-data leaks. A dynamic outcome measure, the overall effectiveness metric (OEM), was conceived to prospectively monitor the effectiveness of our interventions. An OEM ≥1 indicates engagement and thereby improvement, whereby <1 indicates no change compared with baseline. The intervention in PDSA 1 was a success with an OEM of 3.5. Although no actual data leaks occurred, a potential for concern was raised by a senior doctor. This limited engagement with the protocol during PDSA 2 and 3, causing the OEM to decline to <1 towards the end of the project. Sixty percent reported that the protocol saved them time in locating the machine. Individual factors, mainly frustration with the current situation, was a primary driver for the initial engagement among doctors. Although other factors such as senior doctor buy-in, may play a greater role in directing longevity of a technology-based quality improvement solution.